SCALING SOCIAL IMPACT: A LONGITUDINAL ANALYSIS OF SUSTAINABLE BUSINESS MODELS FOR WASTE BANK SOCIAL ENTERPRISES IN URBAN INDONESIA - Hilda Yuliastuti; Priya Patel; David Green (Journal of Social Entrepreneurship and Creative Technology, 2025)
Waste Bank Social Enterprises (WBSEs) are crucial for addressing urban waste challenges in Indonesia but struggle with scalability and financial sustainability. Many fail to move beyond micro-scale operations, limiting their social impact. This study identifies the business model characteristics that enable WBSEs to sustainably scale. It analyzes the evolutionary process of their business models over time. A 36-month longitudinal, mixed-methods study was conducted on twelve urban Indonesian WBSEs. We combined quantitative performance metrics with 72 semi-structured interviews to analyze their scaling trajectories. Findings reveal a stark divergence. Most WBSEs stagnated, trapped by a precarious aggregation-only model. The Rapidly Scaling enterprises were universally differentiated by a strategic pivot: adopting value-adding processing. This transformation allowed them to exit the low-value commodity trap and secure stable, high-value industrial contracts. Sustainable scaling is contingent upon a fundamental business model transformation from a passive collector to an active producer. This evolution from a community project to a market-integrated social enterprise is essential for financial resilience and amplifying social impact.